Modified straw fiber gradient stiffness anti-cracking asphalt pavement structure and construction method
Patent Information
- Application Number
- CN202611132466.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]然而,现有技术仍存在以下不足:一是秸秆纤维在沥青路面中的研究多集中于面层或普通沥青混合料,未专门应用于低模量应力吸收层;二是未将秸秆纤维增强应力吸收层与梯度刚度结构系统整合;三是层间功能构建层的系统设计仍有待完善;四是缺乏面向工程应用的系统化结构设计方案
(1)通过三层梯度模量匹配设计,有效避免了层间刚度突变引发的二次应力集中,实现应力平顺传递,显著降低了层间剪应力;
Smart Images

Figure CN122899102A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering technology, and in particular to a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure and construction method. Background Technology
[0002] Semi-rigid base asphalt pavements have been widely used in high-grade highways in China due to their high strength, high load-bearing capacity, and economy. However, due to the inherent drying and thermal shrinkage characteristics of their base materials, shrinkage cracks are inevitable. Under repeated traffic loads and temperature stresses, these base cracks irreversibly reflect upwards to the asphalt surface layer, forming reflective cracks. The appearance of reflective cracks not only damages the integrity of the pavement and reduces its load-bearing capacity, but also provides channels for moisture intrusion, leading to secondary diseases such as base softening, pumping, and potholes, severely limiting the service life of the pavement structure.
[0003] Engineering practice shows that insufficient interlayer bonding and interlayer water damage are among the main causes of accelerated reflective crack propagation. Especially in areas with heavy traffic, large temperature differences, or high humidity and rainfall, traditional single tack coats cannot simultaneously meet the comprehensive requirements of bonding, stress relief, water damage resistance, shear resistance, and durability. Installing stress-absorbing layers is one of the main measures to delay reflective cracking. Rubber-reinforced asphalt stress-absorbing layer technology reduces horizontal shear stress generated by load and temperature by inserting a highly elastic transition zone between the base course and the surface course, thus delaying crack propagation. Fiber-reinforced rubber-reinforced asphalt stress-absorbing layers have been applied in engineering projects, using intelligent synchronous sealing vehicles to form a dense asphalt film to block rainwater penetration and inhibit crack reflection. However, existing fiber-reinforced stress-absorbing layers mostly use synthetic fibers, glass fibers, or basalt fibers, which have limitations such as high cost, large carbon footprint, and poor biodegradability.
[0004] Meanwhile, the resource utilization of agricultural waste has become an important direction for the construction of green highways. Wheat straw, as one of the largest agricultural by-products produced annually in my country, has long been disposed of by burning, causing serious environmental pollution and resource waste. Therefore, developing a new type of fiber material that is both economical and environmentally friendly, and can effectively improve the crack resistance of stress-absorbing layers, has significant engineering value and practical significance.
[0005] Previous studies have shown that wheat straw flakes (WSF) possess suitable heat resistance in the 130-160℃ range and can form a three-dimensional network structure in asphalt mixtures, significantly improving high and low temperature performance. However, the inherent hydrophilicity of WSF limits the potential for improving its water stability. Silane coupling agent modification has been proven to effectively improve fiber-matrix adhesion and enhance interfacial bonding strength; the asphalt-aggregate interfacial adhesion grade can be improved by 1-2 levels after silanization modification.
[0006] However, existing technologies still have the following shortcomings: First, research on straw fiber in asphalt pavement is mostly focused on surface layers or ordinary asphalt mixtures, and has not been specifically applied to low modulus stress-absorbing layers; second, straw fiber-reinforced stress-absorbing layers have not been integrated with gradient stiffness structural systems; third, the system design of interlayer functional building layers still needs improvement; and fourth, there is a lack of systematic structural design schemes oriented towards engineering applications.
[0007] Therefore, there is an urgent need for a method that combines crack resistance, environmental friendliness, and engineering economy to solve the above-mentioned technical problems. Summary of the Invention
[0008] The purpose of this invention is to provide a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure and construction method. Through a three-layer gradient modulus matching design, secondary stress concentration caused by abrupt changes in interlayer stiffness is effectively avoided, achieving smooth stress transfer and significantly reducing interlayer shear stress. Modified wheat straw fibers form a stable three-dimensional network structure in the stress-absorbing layer, dissipating crack propagation energy through multiple mechanisms such as crack bridging, stress redistribution, and fiber pull-out, significantly improving the low-temperature crack resistance of the pavement structure. The three functional building layers achieve synergistic effects of enhanced bonding, water-blocking seal, shear and skid resistance, and interface reinforcement, effectively improving interlayer bond strength and water stability.
[0009] To achieve the above objectives, this invention provides a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure, comprising, from bottom to top, a semi-rigid base layer, a bottom layer, a middle layer, and a surface layer, with functional building blocks between the layers; the bottom layer is a modified wheat straw fiber reinforced low-modulus stress-absorbing layer, the middle layer is a fiber-modified asphalt medium-modulus layer, and the surface layer is a nano-modified high-modulus asphalt surface layer, with a dynamic modulus ratio of (0.25-0.4):(0.5-0.7):1; the raw material asphalt mixture of the bottom layer contains modified wheat straw fiber, with the amount of modified wheat straw fiber being 0.2-0.35% of the total mass of the asphalt mixture.
[0010] Preferably, the wheat straw fiber in the modified wheat straw fiber has a length of 6mm ± 1mm and a moisture content of ≤12%.
[0011] Preferably, the method for preparing modified wheat straw fiber includes the following steps: Step 1, Alkali Treatment: Crush the wheat straw fiber, immerse the crushed wheat straw fiber in NaOH solution, and treat it in a constant temperature water bath to obtain alkali-treated wheat straw fiber; Step 2: After drying the alkali-treated wheat straw fiber, microwave treatment is carried out, and KH-570 ethanol solution is sprayed on the same time to obtain modified wheat straw fiber.
[0012] Preferably, in step one, the concentration of the NaOH solution is 5-8%, the temperature of the constant temperature water bath is 60℃, and the time is 60-90 min.
[0013] Preferably, in step two, the microwave treatment conditions are: microwave frequency 2450MHz, power 400-600W, temperature 70-80℃, time 5-10min; the mass fraction of KH-570 ethanol solution is 2-3.5%, and the surface contact angle of the modified wheat straw fiber is ≥100°.
[0014] Preferably, the modified wheat straw fiber reinforced low-modulus stress-absorbing layer also includes rubber-modified asphalt and aggregates, with the rubber-modified asphalt being applied at a rate of 2.2-2.6 kg / m³. 2 The rubber-modified asphalt contains 18-22% rubber powder and has an asphalt grade of PG64-28 or PG70-28; the aggregate is 9.5-13.2mm single-size premixed crushed stone, with a spreading rate of 15-22 kg / m³. 2 The gravel coverage rate is 80%-90%.
[0015] Preferably, the interlayer functional construction layer includes a bottom functional construction layer, an intermediate functional construction layer, and a surface functional construction layer; The bottom functional building layer is set between the semi-rigid base course and the bottom course. The bottom functional building layer is formed by simultaneously spreading high-viscosity modified emulsified asphalt and premixed crushed stone. The intermediate functional building layer is set between the bottom layer and the middle layer. The intermediate functional building layer is formed by spraying SBS modified emulsified bitumen and interlining polyester fiber mesh. The surface functional building layer is set between the intermediate layer and the surface layer, and is formed by thermal spraying of SBS modified high-viscosity asphalt.
[0016] The above-mentioned construction method for a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure includes the following steps: S1. Clean the surface of the semi-rigid base layer and spray it with tack coat oil. Lay the bottom functional building layer on the surface of the semi-rigid base layer. S2. Prepare modified wheat straw fiber, and use an intelligent synchronous sealing vehicle to simultaneously spread and compact heated rubber-modified asphalt, aggregate and modified wheat straw fiber on the surface of the bottom functional building layer to form the bottom layer; S3. Lay an intermediate functional building layer on the bottom surface, and lay a middle layer on the surface of the intermediate functional building layer; S4. Lay a surface functional building layer on the middle layer surface, and lay a surface layer on the surface functional building layer. S5. After the surface layer is laid, overall compaction and curing are carried out to obtain a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure.
[0017] Preferably, in S2, the heating temperature of the rubber-modified asphalt is 185-200℃, and the modified wheat straw fiber is simultaneously added to the sealing vehicle spraying mechanism using an air conveying system; the bottom layer is rolled by a 25-ton tire roller 2-3 times, and the rolling temperature is not lower than 130℃.
[0018] Preferably, in S5, the freeze-thaw splitting strength ratio of the prepared modified straw fiber gradient stiffness crack-resistant asphalt pavement structure is ≥80%, and the interlayer shear strength is ≥0.8MPa.
[0019] Therefore, the present invention, employing the above-mentioned modified straw fiber gradient stiffness crack-resistant asphalt pavement structure and construction method, has the following beneficial effects: (1) Through the three-layer gradient modulus matching design, the secondary stress concentration caused by the sudden change in interlayer stiffness is effectively avoided, the stress is smoothly transferred, and the interlayer shear stress is significantly reduced. (2) Wheat straw fiber was modified by a two-step method of alkali treatment and microwave-assisted silane coupling agent grafting, which changed the fiber surface from hydrophilic to hydrophobic and oleophilic, significantly improving the interfacial compatibility and thermal stability of the fiber and asphalt, and effectively preventing the thermal degradation of the fiber during the high-temperature mixing of asphalt mixture. (3) Modified wheat straw fiber forms a stable three-dimensional network structure in the stress absorption layer, which dissipates crack propagation energy through multiple mechanisms such as bridging cracks, stress redistribution and fiber pull-out, thus significantly improving the low-temperature crack resistance of the pavement structure. (4) The three-layer functional building layer realizes the synergistic effect of multiple functions such as enhanced bonding, water-blocking sealing, shear and anti-slip, and interface reinforcement, which effectively improves the interlayer bonding strength and water stability. (5) Replacing synthetic fibers with agricultural waste wheat straw realizes the resource utilization of agricultural waste. Microwave-assisted grafting process significantly reduces energy consumption and has both environmental and economic benefits.
[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to the present invention; Figure 2 This is a flow chart of the modified wheat straw fiber preparation process of the present invention; Figure 3 This is a graph showing the relationship between the critical network concentration and the complex dynamic modulus of the modified wheat straw fiber of this invention. Figure 4 This is the effect curve of the three-layer modulus matching window of the present invention on the maximum principal stress at the bottom of the surface layer; Figure 5This is a flowchart of the response surface methodology for optimizing experimental design according to the present invention; Figure 6 These are SEM comparison images of the microstructure of wheat straw fibers obtained by different processing methods according to the present invention. Figure 7 This is a diagram illustrating the mechanism for suppressing the propagation of reflective cracks in this invention. Detailed Implementation
[0022] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.
[0023] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0024] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.
[0025] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.
[0026] like Figure 1 As shown, this invention provides a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure, which consists of the following components from bottom to top: (1) Semi-rigid base layer: set at the bottom layer; (2) Substrate functional building layer: formed by synchronously spreading high-viscosity modified emulsified asphalt and premixed crushed stone, and set on the semi-rigid base course; (3) Bottom layer: namely, modified wheat straw fiber reinforced low modulus stress absorption layer, which is set on the bottom functional building layer, and its dynamic modulus is 1500-2500MPa; (4) Intermediate functional building layer: formed by spraying SBS modified emulsified asphalt and sandwiching polyester fiber mesh, and set on the stress absorption layer; (5) Middle layer: namely, fiber modified asphalt medium modulus layer, which is set on the intermediate functional building layer, and its dynamic modulus is 2500-4000MPa; (6) Surface functional building layer: The surface functional building layer is formed by hot spraying of SBS modified high viscosity asphalt and is set on the medium modulus layer; (7) Surface layer: namely, nano-modified high modulus asphalt surface layer, which is set on the surface functional building layer, and its dynamic modulus is 4000-6000MPa.
[0027] The dynamic modulus ratio of the bottom layer, middle layer, and top layer is (0.25-0.4):(0.5-0.7):1.
[0028] The design principle of the above three-layer modulus matching window is as follows: when the modulus gradient of the surface layer is too large, the tensile stress and stress intensity factor in the pavement structure both increase accordingly. By setting a modulus transition layer (middle layer), the shear stress of the surface layer can be effectively reduced, secondary stress concentration caused by abrupt changes in interlayer stiffness can be avoided, and a smoother modulus transition from an elastic body to a rigid body can be achieved. Figure 4 The influence curve of the three-layer modulus matching window on the maximum principal stress at the bottom of the surface layer further verifies the design principle.
[0029] Interlayer functional building blocks are set between the three layers mentioned above. Each interlayer functional building block can be selectively set with different materials and process parameters according to the differences in actual needs. The interlayer functional building blocks can achieve multiple functions such as enhancing bonding, water-blocking sealing, shear and anti-slip, stress absorption, interface reinforcement, and anti-reflective cracking, ensuring that the interface condition is controllable, the material usage is verifiable, and the construction parameters are traceable.
[0030] The base layer is prepared from modified wheat straw fiber, rubber-modified asphalt, and aggregates, with the rubber-modified asphalt being applied at a rate of 2.2-2.6 kg / m³. 2 The rubber-modified asphalt contains 18-22% rubber powder and has an asphalt grade of PG64-28 or PG70-28; the aggregate is 9.5-13.2mm single-size premixed crushed stone, with a spreading rate of 15-22 kg / m³. 2 The gravel coverage rate is 80%-90%. The amount of modified wheat straw fiber added is 0.2-0.35% of the total mass of the mixture.
[0031] Modified wheat straw fiber can play the following roles in the bottom layer: (1) Bridging cracks: the fiber crosses both sides of the micro-crack and consumes the crack propagation energy by pulling out or breaking; (2) Three-dimensional network reinforcement: the fiber forms a randomly distributed spatial network, which improves the overall toughness and stress transmission uniformity; (3) Stress redistribution: stress concentration occurs at the fiber end, which forces the crack propagation path to deflect and prolongs the propagation path; (4) Adhesion and adsorption: the fiber surface adsorbs asphalt, which increases the effective asphalt film thickness.
[0032] The modified wheat straw fiber content of 0.20%-0.35% corresponds to the critical content range for wheat straw to form a stable three-dimensional network structure in rubber asphalt, such as... Figure 3 The curves showing the relationship between the critical network concentration and the complex dynamic modulus of modified wheat straw fiber indicate that when the modified wheat straw fiber content reaches approximately 0.20%, the complex modulus shows a significant jump, indicating that the fiber has formed a three-dimensional spatial network structure. After the content exceeds 0.35%, the complex modulus gradually decreases. This is because excessive incorporation leads to fiber agglomeration, resulting in a decrease in modulus. Therefore, the optimal content range is determined to be 0.20%-0.35%. When the fiber content is within this range, the wheat straw fibers interlock in the mixture to form a spatial network structure, dissipating crack propagation energy through multiple mechanisms such as bridging cracks, stress redistribution, and fiber pull-out. The mechanism is as follows: Figure 7 As shown.
[0033] In the priority ranking of factors affecting fiber parameters, fiber content > moisture content > length. Therefore, fiber content and moisture content should be the focus of control during construction.
[0034] Modified wheat straw fiber was prepared using a two-step hydrophobic modification process involving alkali treatment and microwave-assisted silane coupling agent grafting. Figure 2 The specific steps are as follows: Step 1, Alkali Treatment: Removes impurities and exposes the rough surface; Wheat straw was mechanically crushed into segments of 6mm ± 1mm in length. These segments were then immersed and stirred in a 5%-8% NaOH solution at 60℃ for 60-90 minutes to thoroughly remove the hemicellulose and waxy layer from the fiber surface. The alkali-treated fibers were repeatedly rinsed with deionized water until neutral and then dried at 80℃ to constant weight.
[0035] Alkali treatment can remove hemicellulose and wax layers from the fiber surface, exposing a rough, micron-sized groove structure. It can also improve the surface cleanliness and hydroxyl density, providing more reaction sites for subsequent silane coupling agent grafting, thereby improving the compatibility between the fiber and the pitch matrix. Previous studies have shown that graded acid-alkali treatment of straw fiber surfaces, followed by the use of γ-aminopropyltriethoxysilane coupling agents, has led to a comprehensive improvement in the mechanical properties of composite materials.
[0036] Step 2: Microwave-assisted grafting of silane coupling agent, hydrophobic modification, and improved compatibility; Alkali-treated and dried straw fibers are placed in a microwave reactor with a microwave frequency of 2450MHz, a power of 400-600W, a temperature of 70-80℃, and a time of 5-10min. At the same time, a 2%-3.5% (w / w) ethanol solution of γ-methacryloyloxypropyltrimethoxysilane (KH-570) is sprayed evenly to ensure that the silane coupling agent evenly covers the fiber surface.
[0037] After the methoxy group of KH-570 is hydrolyzed, it generates silanol group, which undergoes a condensation reaction with the hydroxyl group activated on the fiber surface after alkali treatment to form Si-O-fiber chemical bond; its acryloyloxy organic functional group can undergo physical adsorption or chemical bonding with the polar components in the asphalt, firmly anchoring the fiber in the asphalt matrix and forming a molecular bridging structure.
[0038] Compared with traditional thermochemical reactions, microwave-assisted grafting has significant advantages such as uniform overall heating and short reaction time. Combined with silane coupling agent grafting treatment, the fiber grafting effect can be improved, while reducing energy consumption by about 30%.
[0039] After the above two modification steps, the surface contact angle of the modified wheat straw fiber can be increased from <30° in its natural state to ≥100°. Three experiments were conducted on the above operations, and the results are as follows: Figure 6 As shown, Figure 6 Images (a), (d), and (g) in the diagram represent the surface morphology of the untreated fibers. Figure 6 Images (b), (e), and (h) in the diagram show the surface morphology of the fiber after alkali treatment. Figure 6 Images (c), (f), and (i) in the figure are surface morphology diagrams of fibers covered with a hydrophobic film (i.e., subjected to alkali treatment and microwave-assisted grafting treatment), by... Figure 6 It can be seen that the surface morphology of the fiber changed significantly after the hydrophobic film was applied, indicating that KH-570 grafting was successful. Silanization treatment can also form a stable and dense thermal stability network on the fiber surface, significantly increasing the thermal decomposition temperature of the fiber and preventing thermal degradation of the fiber during the high-temperature mixing of asphalt mixtures.
[0040] The surface contact angles of natural fibers and modified fibers, as well as the high-temperature rheological properties and thermal decomposition behavior of the asphalt system before and after modification, were compared through experiments. The specific experimental results are shown in Table 1.
[0041] Table 1. Performance test results of natural fibers and modified fibers
[0042] After two-step hydrophobic modification, the surface contact angle of wheat straw fiber increased from 28° to 105°, transforming from a strongly hydrophilic state to a hydrophobic and oleophilic state. This effectively enhanced the interfacial bonding between the fiber and the asphalt and prevented water intrusion. This led to an increase of approximately 32% in the complex modulus of the modified asphalt system at 60°C and a decrease of approximately 7° in the phase angle, significantly improving the material's high-temperature deformation resistance and elastic recovery performance. At the same time, the thermal decomposition temperature increased by 40°C, indicating that KH-570 formed stable chemical bonds and a dense hydrophobic network on the fiber surface, thereby greatly improving the material's thermal stability and overall durability.
[0043] In the initial mix design stage, the following methods are adopted: Figure 5 The response surface methodology shown is used to optimize the modified wheat straw fiber content: Step A1: A multi-factor, multi-level experimental design was conducted using a Box-Behnken design. Factors included A = fiber content (0.20%-0.35%) and B = asphalt application rate (2.2-2.6 kg / m³). 2 C = Crushed stone spreading rate (15-22 kg / m³) 2 The levels of each factor are shown in Table 2.
[0044] Table 2. Factors affecting the fiber content of wheat straw
[0045] Step A2: Prepare stress-absorbing layer specimens according to the design, and conduct indoor semi-circular bending tests to determine fracture energy, freeze-thaw splitting tests to determine freeze-thaw splitting strength ratio (TSR), and direct shear tests to determine interlaminar shear strength. Specific data are shown in Table 3.
[0046] Table 3 Test Results
[0047] Step A3: Use data analysis software to perform multivariate regression fitting on the experimental data, establish a quadratic polynomial response surface model, and use the expectation function method for global optimization. The optimization algorithm gives three sets of optimal solutions as shown in Table 4.
[0048] Table 4 Optimal Solution for Modified Wheat Straw Fiber Content
[0049] Based on the combined optimal solutions from the three sets of data, the recommended parameter ranges are determined as follows: fiber content: 0.24%-0.27%; asphalt application rate: 2.4-2.5 kg / m³. 2 Crushed stone spreading rate: 18.5-19.5 kg / m³ 2 .
[0050] Step A4: According to the optimized recommended parameters, the fiber content is 0.25% and the asphalt application rate is 2.45 kg / m³.2 Crushed stone spreading rate: 19.0 kg / m³ 2 Three sets of independent specimens were prepared for verification experiments. The results are compared with the model predictions in Table 5.
[0051] Table 5. Comparison of verification experiment results with model predictions
[0052] As shown in Table 5, the results of the verification experiment are in good agreement with the model predictions, with relative errors all within 1.3%, confirming that the established response surface model has high prediction accuracy and engineering reliability.
[0053] Furthermore, by controlling the content of modified wheat straw fiber within the range of 0.2-0.35%, the basic conditions for fiber network formation are ensured, while avoiding excessive asphalt mastic stiffness. The integrated spreading process using a synchronous sealing vehicle can achieve uniform dispersion of modified wheat straw fiber and avoid the viscosity increase problem caused by premixing modified wheat straw fiber.
[0054] The pavement performance of the two types of pavement with and without a bottom layer structure was compared and analyzed, and the results are shown in Table 6.
[0055] Table 6 Performance test results with and without underlying configuration
[0056] Compared with direct overlay structures without a base layer, the addition of a dense-structure UFAC stress-absorbing layer reduces the vertical compressive stress, maximum principal stress, and maximum shear stress at the bottom of the asphalt overlay by 23.5%, 32.7%, and 29.4%, respectively. The interlayer shear strength increases from approximately 0.52 MPa to approximately 0.87 MPa, and the interlayer shear strain decreases by approximately 36%. The results indicate that the three-layer gradient stiffness structure, by controlling the modulus difference within a reasonable range through a modulus matching window, can effectively alleviate and release interlayer stress, enhance interlayer bonding, effectively avoid stress concentration caused by abrupt changes in interlayer stiffness, and significantly reduce the risk of reflective cracking.
[0057] After determining the optimal mix ratio for the base layer, the interlayer connections between pavement structures need to be designed. The coordinated operation of the base, intermediate, and surface layers relies on reliable interlayer interfaces. Different material and process parameters can be selectively set for each interlayer functional building layer according to actual needs. In accordance with the requirements of relevant standards T / XZBX0175-2025 and T / SDHTS00013-2025, interlayer functional building layers are set between each layer of the pavement structure. The structural combinations and material types of each interlayer functional building layer are shown in Table 7.
[0058] Table 7. Interlayer Functional Construction Layer Structure Combinations and Material Types
[0059] The construction method of the modified straw fiber gradient stiffness crack-resistant asphalt pavement structure of the present invention includes the following steps: Step S1: Semi-rigid base treatment.
[0060] Clean the surface of the base layer of dust and mud, blow away the dust, ensure the surface is dry, spray the tack coat, lay the base functional building layer, and wait for demulsification and drying.
[0061] Step S2: Preparation of modified wheat straw fiber.
[0062] S2-1: Mechanically crush the cleaned and dried wheat straw into 6mm±1mm segmented fibers; S2-2: Place the crushed fibers in a 5%-8% NaOH solution, stir in a 60℃ water bath for 60-90 minutes, rinse until neutral, and then dry. S2-3: Place the alkali-treated fibers into a microwave reactor. Use a microwave frequency of 2450MHz, a power of 400-600W, a temperature of 70-80℃, and a time of 5-10min. Simultaneously spray with a 2%-3.5% KH-570 ethanol solution. After drying, seal and store for later use.
[0063] Step S3: Laying of modified wheat straw fiber reinforced low modulus stress-absorbing layer.
[0064] Heat the rubber-modified asphalt to 185-200℃ and spray it evenly onto the surface of the base layer where the functional building layer has been laid, at a rate of 2.2-2.6 kg / m². 2 Simultaneously spread 9.5-13.2mm premixed crushed stone at a rate of 15-22 kg / m³. 2 The aggregate coverage is approximately 80%-90%; simultaneously, modified wheat straw fiber is sprayed at a concentration of 0.20%-0.35% of the total mass of the mixture. It is recommended to use an intelligent synchronous sealing vehicle to achieve simultaneous and integrated application of asphalt, aggregate, and fiber. Subsequently, a 25-ton pneumatic tire roller is used for 2-3 passes to ensure the aggregate is fully embedded in the rubber asphalt film, with a compaction temperature not lower than 130℃.
[0065] Step S4: Construction of the intermediate functional building layer.
[0066] Spray 1.0-1.5 kg / m² of SBS modified emulsified asphalt onto the surface of the compacted stress-absorbing layer. 2 Simultaneously, polyester fiber mesh is laid, allowing the fiber mesh to integrate into the asphalt membrane to form a reinforcing layer.
[0067] Step S5: Construction of fiber-modified asphalt intermediate modulus layer.
[0068] Mix AC-20 or AC-25 graded asphalt mixtures, adding 0.20%-0.35% fiber during the mixing process, with the ratio of straw fiber to polyester fiber being 1:1.5. The mixing temperature is 170-180℃, and the mixture is spread and compacted to a thickness of 8-12cm.
[0069] Step S6: Construction of the surface functional building layer.
[0070] Spray 0.6-1.0 kg / m² of SBS modified high-viscosity asphalt onto the top surface of the intermediate modulus layer. 2 .
[0071] Step S7: Paving of nano-modified high-modulus asphalt surface layer.
[0072] SBS modified asphalt is used with AC-13 or SMA-13 gradation, with 0.2%-0.3% nano-modifier added. The mixing temperature is 175-185℃, and the asphalt is paved and compacted to a thickness of 4-6cm.
[0073] Step S8: Compaction and Curing.
[0074] After each layer is compacted according to specifications, it should be allowed to cure naturally until the road surface temperature drops below 50°C before it can be opened to traffic.
[0075] Example 1 This example describes a newly constructed section of S219 in Kashgar Prefecture, Xinjiang Uygur Autonomous Region. The region has an average annual temperature of 11.7℃, an extreme minimum temperature of -24.4℃, an extreme maximum temperature of 49.1℃, and an average annual rainfall of 30-60 mm. It has a temperate continental arid climate with large diurnal temperature variations and strong solar radiation. The traffic level is medium, with a design service life of 15 years.
[0076] (1) Semi-rigid base treatment: The base layer uses cement-stabilized gravel with a cement content of 5.0%. After 7 days of curing following the completion of the base layer construction, the surface laitance and soil are cleaned, and dust is thoroughly removed using a powerful blower. A tack coat is sprayed, and after demulsification and drying, the functional sub-layer is constructed: high-viscosity modified emulsified asphalt is sprayed at a rate of 1.0 kg / m². 2 Simultaneously spread 4.75-9.5mm premixed crushed stone at a rate of 8kg / m². 2 The crushed stone is embedded in the asphalt membrane by compaction with a light roller, providing a smooth, clean, and well-bonded interface for the subsequent stress-absorbing layer.
[0077] (2) Preparation of modified wheat straw fiber: Wheat straw is sourced from winter wheat in the Kashgar region. It is naturally sun-dried until the moisture content is ≤12%, and then the ears, leaf sheaths, and soil are removed before storage. The straw is then chopped using a straw crusher to a length of 6mm±1mm, and sieved to remove excessively long or short fibers, ensuring uniform fiber length.
[0078] Alkali treatment: Weigh 5 kg of crushed wheat straw fiber and immerse it in a 6% NaOH solution. Stir in a 60℃ constant temperature water bath for 70 min to fully remove the hemicellulose and waxy layer on the fiber surface. After alkali treatment, rinse the fiber repeatedly with deionized water until pH test paper does not change color, and then dry it in an 80℃ forced-air drying oven to constant weight. The alkali-treated fiber is light brown, with clearly exposed surface grooves and significantly improved roughness.
[0079] Microwave-assisted silane grafting: Alkali-treated and dried fibers are evenly spread in a ceramic dish and placed in a microwave reactor. A spraying device is installed inside the microwave cavity, and a 2.5% KH-570 ethanol solution is prepared and the spraying flow rate is adjusted to 10 mL / min. Microwave treatment parameters: temperature 75℃, time 8 min, nitrogen gas is purged into the cavity for protection to prevent fiber oxidation during grafting. After the reaction, the fibers are removed, vacuum dried at 80℃ for 2 hours, and then sealed for storage.
[0080] Tests showed that the contact angle of the modified wheat straw fiber was 102° and the thermal decomposition temperature increased from 215°C to 265°C, indicating that KH-570 successfully grafted a stable Si-O-fiber chemical bond hydrophobic layer onto the fiber surface.
[0081] (3) Substrate construction: The parameters of the underlying material are shown in Table 8: Table 8 Material Parameters
[0082] In this embodiment, the fiber content of 0.25% is within the optimal content range of 0.20%-0.35%. Verified by the complex modulus jump curve of the dynamic shear rheometer, this content point corresponds to the percolation threshold of the fiber's transformation from a dispersed state to a three-dimensional continuous network. The reinforcing effect of bridging cracks and stress redistribution is fully utilized, while avoiding fiber agglomeration and decreased workability caused by excessive content.
[0083] Construction equipment: CL-5300 intelligent synchronous sealing vehicle is selected. The equipment should be equipped with three independent spraying systems for asphalt, crushed stone and fiber, and a fiber airflow conveying device. It relies on compressed air to evenly disperse and spray the fiber onto the surface of the asphalt film to ensure that the fiber does not agglomerate in the rubber asphalt.
[0084] Construction steps: 1. Heat the rubber-modified asphalt to 190±5℃ and pump it to the asphalt tank of the synchronous seal vehicle. The temperature should be strictly controlled between 185-200℃ to avoid excessive viscosity of asphalt and insufficient chip embedding due to low temperature, or asphalt aging due to high temperature.
[0085] 2. Load crushed stone into the crushed stone bin. The crushed stone particle size should be uniform, and the content of oversized particles should be ≤5%. Visual inspection should be carried out on each truck of crushed stone at the construction site. If the content of needle-like and flaky particles exceeds the standard, the material source should be replaced in time.
[0086] 3. Load the modified wheat straw fiber into the fiber addition hopper, set the conveying rate according to the matching relationship between the conveying rate and the vehicle driving speed, and ensure that the dosage deviation is controlled within ±5% of the set value.
[0087] 4. The sealing vehicle travels at a constant speed of 4.5 km / h, and the application rate of rubber-modified asphalt is 2.4 kg / m³. 2 The amount of gravel spread is 18 kg / m³. 2 Ideally, the gravel coverage rate should be controlled between 80% and 90%.
[0088] 5. Immediately after the synchronous sealing vehicle, a 25-ton pneumatic tire roller should be used to compact the road surface twice, with the compaction direction from the low side to the high side of the road surface. The compaction speed should be 5 km / h, and the compaction temperature should be no less than 130℃.
[0089] 6. After compaction, the crushed stone should be embedded to a depth of approximately 2 / 3, with the exposed portions evenly distributed but without overlap, and the asphalt film continuous and unbroken. Allow the mixture to stand for 4 hours until the stress-absorbing layer temperature drops below 50℃ before proceeding to the next construction step.
[0090] (4) Construction of intermediate functional building layer: SBS-modified emulsified asphalt was sprayed onto the surface of the compacted stress-absorbing layer at a rate of 1.2 kg / m². 2 The spraying operation utilizes an intelligent asphalt distributor, with the spraying temperature controlled at 70-80℃ to ensure uniform and thorough application of the emulsified asphalt. Before the emulsified asphalt breaks down, a polyester fiber mesh is manually laid, with a directional overlap width of no less than 10cm and a longitudinal overlap length of no less than 30cm. After laying, a light roller is used for static compaction once to ensure the fiber mesh is fully embedded in the asphalt film, forming a continuous reinforcement layer.
[0091] (5) Intermediate layer paving: The mixture uses AC-20 gradation, SBS modified asphalt, and polyester fiber with a length of 12mm and a dosage of 0.30%.
[0092] Mixing: An intermittent mixing plant is used to produce the mixture. The mixing process parameters are as follows: First, the fiber is added to the mixing tank and dry-mixed with the aggregate for 5 seconds to initially disperse the fiber in the aggregate. Then, asphalt is added for wet mixing for 40 seconds to ensure that the fiber is evenly distributed in the mixture. The aggregate heating temperature is 180℃, the asphalt heating temperature is 165℃, and the discharge temperature is controlled at 175℃.
[0093] Paving and compaction: The temperature of the mixture upon arrival at the site should not be lower than 170℃, the paving temperature should be 165℃, and the loose paving thickness multiplied by the loose paving coefficient should be controlled in 10cm increments. Compaction combination: Two initial compactions with a double-drum roller, four secondary compactions with a rubber-tired roller, and one final compaction with a double-drum roller for finishing. The degree of compaction should be controlled to above 98.2% according to the Marshall compaction standard, with no segregation or wheel tracks on the surface.
[0094] (6) Construction of the functional building layer: SBS modified high-viscosity asphalt was sprayed onto the top surface of the compacted intermediate modulus layer at a rate of 0.8 kg / m². 2 The spraying temperature is controlled between 165-175℃. During construction, a computer-controlled asphalt distributor is used, automatically controlling the spraying rate with a deviation of ≤±0.05kg / m³. 2 Ensure even spraying, with no gaps or overlaps. Avoid vehicle traffic before laying the topcoat after spraying to prevent contamination between layers.
[0095] (7) Surface layer paving: The gradation uses SMA-13, and the asphalt uses SBS modified asphalt. An additional 0.3% nano-ZnO is added to the asphalt. The nano-ZnO is first sheared and dispersed with the SBS modified asphalt at 180℃ for 30 minutes using a high-speed shear mill with a shearing speed of not less than 5000 r / min to ensure that the nanoparticles are uniformly dispersed in the asphalt before the SMA mixture is produced.
[0096] Fiber stabilizer: lignin fiber, dosage 0.4% (percentage of total mass of mixture), used to adsorb asphalt and stabilize the SMA skeleton structure.
[0097] Mixing: The mixing temperature is 185℃. Since nano-modified asphalt has a higher temperature, the heating rate must be controlled to not exceed 5℃ / min to prevent localized overheating and aging of the asphalt. Discharge temperature is 180℃, paving temperature is 175℃, and the loose paving thickness is controlled at 5cm plus the loose paving coefficient.
[0098] Compaction: Initial compaction is performed twice using a double-drum roller with vibration, followed by four passes using a rubber-tired roller. Final compaction is performed once using a double-drum roller with static compaction. Construction vehicles are allowed to pass only when the road surface temperature drops below 70℃ after final compaction, but official opening to traffic is only permitted when the temperature drops below 50℃.
[0099] (8) Performance testing: Core samples were taken from the test section and processed into three-layer integral composite specimens (surface layer + intermediate modulus layer + stress-absorbing layer + functional layer with complete adhesion). Indoor performance tests were conducted according to typical asphalt mixture testing methods used in the Xinjiang Uygur Autonomous Region. The test results are shown in Table 9. Table 9 Indoor performance test results
[0100] As shown in Table 9, the engineering practice of Example 1 in a new national highway construction project in Kashgar, Xinjiang Uygur Autonomous Region, demonstrates that after adopting the modified wheat straw fiber reinforced gradient stiffness crack-resistant asphalt pavement structure, the low-temperature fracture energy is increased by approximately 40%, the interlayer shear strength is ≥0.87MPa, and the high-temperature dynamic stability is 8120 cycles / mm. All performance indicators meet or exceed the design requirements. This pavement structure integrates several key technologies, including three-layer gradient modulus matching, a three-dimensional network reinforced stress-absorbing layer of wheat straw fiber, and a nano-modified surface layer. It provides a replicable engineering construction solution for the crack resistance problem of semi-rigid base asphalt pavements in the dry, cold, and windy climate region of Xinjiang Uygur Autonomous Region, characterized by large diurnal temperature differences, strong solar radiation, and frequent sandstorms.
[0101] Example 2 Road overlay and renovation project: A provincial highway maintenance project in Shandong Province. The original road surface was cement concrete, which had developed defects such as broken slabs and misalignment. The structure of this invention was used for overlay, with a designed total overlay thickness of 17cm, and the traffic level was heavy traffic.
[0102] (1) Treatment of old road surface: Mill 2cm of the old cement pavement surface, remove loose dust, spray interface treatment agent, and pour a 1cm thick rubber asphalt mortar leveling layer before laying the stress-absorbing layer.
[0103] (2) Material adjustment: Due to heavy traffic demands, the grade of the stress-absorbing layer rubber asphalt was increased to PG76-28. The preparation steps for the modified wheat straw fiber were the same as in Example 1, with a dosage of 0.30%. A layer of fiberglass grid was added to the intermediate functional building layer, placed on top of the polyester fiber mesh, to form a double-layer reinforcement.
[0104] (3) Construction parameters: The aggregate size of the bottom functional building layer was changed to a mixture of 9.5-13.2mm and 4.75-9.5mm, with a spreading rate of 20kg / m³. 2 The intermediate modulus layer is 12cm thick, and the surface layer is 5cm thick. The remaining construction parameters are basically the same as in Example 1.
[0105] (4) Performance verification: Core samples were taken from the test section for indoor performance testing, and the results are shown in Table 10.
[0106] Table 10 Indoor performance test results
[0107] As shown in Table 10, the engineering practice of Example 2 in the reconstruction project of an old provincial highway (heavy traffic level) in Shandong Province shows that after adopting the modified wheat straw fiber reinforced gradient stiffness crack-resistant asphalt pavement structure, the low-temperature fracture energy is increased by about 30% (reaching 2.65 kJ / m).2 The interlayer shear strength reaches 0.93 MPa, the high-temperature dynamic stability reaches 7080 cycles / mm, and no cracks appeared in the accelerated loading test (conventional structures will crack after 30,000 cycles). All performance indicators meet or exceed the design requirements. The pavement structure also has excellent crack resistance, water damage resistance, shear resistance and rutting resistance in the heavy traffic road overlay scenario, verifying its wide applicability and replicability in different engineering types and traffic levels.
[0108] Therefore, this invention employs a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure and construction method. Through a three-layer gradient modulus matching design, it effectively avoids secondary stress concentration caused by abrupt changes in interlayer stiffness, achieving smooth stress transfer and significantly reducing interlayer shear stress. The modified wheat straw fibers form a stable three-dimensional network structure in the stress-absorbing layer, dissipating crack propagation energy through multiple mechanisms such as crack bridging, stress redistribution, and fiber pull-out, significantly improving the low-temperature crack resistance of the pavement structure. The three functional building layers achieve synergistic effects of enhanced bonding, water-blocking seal, shear and skid resistance, and interface reinforcement, effectively improving interlayer bond strength and water stability.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A modified straw fiber gradient stiffness crack-resistant asphalt pavement structure, characterized in that: From bottom to top, the layers are a semi-rigid base course, a bottom course, a middle course, and a top course, with functional building blocks between the layers. The bottom course is a modified wheat straw fiber reinforced low-modulus stress-absorbing layer, the middle course is a fiber-modified asphalt medium-modulus layer, and the top course is a nano-modified high-modulus asphalt surface course. The dynamic modulus ratio of the bottom course, middle course, and top course is (0.25-0.4):(0.5-0.7):
1. The asphalt mixture used as the base course contains modified wheat straw fiber, and the amount of modified wheat straw fiber is 0.2-0.35% of the total mass of the asphalt mixture.
2. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: The modified wheat straw fiber has a length of 6mm ± 1mm and a moisture content of ≤12%.
3. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: The preparation method of modified wheat straw fiber includes the following steps: Step 1, Alkali Treatment: Crush the wheat straw fiber, immerse the crushed wheat straw fiber in NaOH solution, and treat it in a constant temperature water bath to obtain alkali-treated wheat straw fiber; Step 2: After drying the alkali-treated wheat straw fiber, microwave treatment is carried out, and KH-570 ethanol solution is sprayed on the same time to obtain modified wheat straw fiber.
4. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: In step one, the concentration of the NaOH solution is 5-8%, the temperature of the constant temperature water bath is 60℃, and the time is 60-90 minutes.
5. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: In step two, the microwave treatment conditions are as follows: microwave frequency 2450MHz, power 400-600W, temperature 70-80℃, time 5-10min; mass fraction of KH-570 ethanol solution is 2-3.5%, and the surface contact angle of modified wheat straw fiber is ≥100°.
6. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: The modified wheat straw fiber-reinforced low-modulus stress-absorbing layer also includes rubber-modified asphalt and aggregates, with the rubber-modified asphalt being applied at a rate of 2.2-2.6 kg / m³. 2 The rubber-modified asphalt contains 18-22% rubber powder and has an asphalt grade of PG64-28 or PG70-28; the aggregate is 9.5-13.2mm single-size premixed crushed stone, with a spreading rate of 15-22 kg / m³. 2 The gravel coverage rate is 80%-90%.
7. The modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 1, characterized in that: The interlayer functional construction layer includes a bottom functional construction layer, an intermediate functional construction layer, and a surface functional construction layer; The bottom functional building layer is set between the semi-rigid base course and the bottom course. The bottom functional building layer is formed by simultaneously spreading high-viscosity modified emulsified asphalt and premixed crushed stone. The intermediate functional building layer is set between the bottom layer and the middle layer. The intermediate functional building layer is formed by spraying SBS modified emulsified bitumen and interlining polyester fiber mesh. The surface functional building layer is set between the intermediate layer and the surface layer, and is formed by thermal spraying of SBS modified high-viscosity asphalt.
8. A construction method for a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure as described in any one of claims 1-7, characterized in that: Includes the following steps: S1. Clean the surface of the semi-rigid base layer and spray it with tack coat oil. Lay the bottom functional building layer on the surface of the semi-rigid base layer. S2. Prepare modified wheat straw fiber, and use an intelligent synchronous sealing vehicle to simultaneously spread and compact heated rubber-modified asphalt, aggregate and modified wheat straw fiber on the surface of the bottom functional building layer to form the bottom layer; S3. Lay an intermediate functional building layer on the bottom surface, and lay a middle layer on the surface of the intermediate functional building layer; S4. Lay a surface functional building layer on the middle layer surface, and lay a surface layer on the surface functional building layer. S5. After the surface layer is laid, overall compaction and curing are carried out to obtain a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure.
9. The construction method of a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 8, characterized in that: In S2, the heating temperature of rubber-modified asphalt is 185-200℃, and the modified wheat straw fiber is simultaneously added to the sealing vehicle spraying mechanism using an air conveying system; the bottom layer is rolled by a 25-ton tire roller 2-3 times, with a rolling temperature of not less than 130℃.
10. The construction method of a modified straw fiber gradient stiffness crack-resistant asphalt pavement structure according to claim 8, characterized in that: In S5, the freeze-thaw splitting strength ratio of the modified straw fiber gradient stiffness crack-resistant asphalt pavement structure prepared is ≥80%, and the interlayer shear strength is ≥0.8MPa.